Fresh Organic Matter Application to Improve Aggregate Stability of Ultisols under Wet Tropical Region - . Yulnafatmawita; Febrian Anggriani (UNIVERSITY OF LAMPUNG, 2013)
Ultisol as a marginal soil has become ‘a hope’ by farmers in Indonesia due to land use change, lately. However, the soil is susceptible to degradation since it has low soil aggregate stability (SAS) as affected by low soil organic matter (SOM) content. A pot trial about application of fresh organic matter (FOM) was aimed to improve SAS of Ultisols under wet tropical rainforest. Three types of FOM (Tithonia diversifolia, Chromolaena odorata, and Gliricidia sepium) at different size (8, 6, 4, 2, and 0.5 cm) were applied for 1% (20 g 2 kg-1 soil), then mixed and incubated for three months. The experimental units were allocated in a completely randomized design at a glasshouse. The results showed that FOM generally increased SOM content, percent aggregation, as well as SAS of the Ultisol. Among the organic matter (OM) sources, tithonia gave the highest SOM content after a 3-month incubation. Within the types of OM source, the smallest OM size applied showed the highest SOM content. Tithonia at 0.5 cm in size gave the highest SOM (3.47%) of the Ultisol and SAS increased by 68% compared to the initial soil. Overall, there was a positive correlation (R2 = 0.43) between SOM content and aggregate stability index, but no correlation (R2=0.04) between SOM content and percent aggregation of the Ultisols.[How to Cite : Yulnafatmawita and F Anggriani. 2013. Fresh Organic Matter Application to Improve Aggregate Stability of Ultisols under Wet Tropical Region. J Trop Soils 18 (1): 33-44. doi: 10.5400/jts.2013.18.1.33][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.33]